A comparative analysis of the regulatory framework governing energy sources: coal and renewable energy - Mvubu, Nkosinathi (My University, 2018)
As a natural resource coal has for a long time been the bedrock of South Africa’s energy sector. South Africa is one of the richest countries in the world in terms of coal deposits. This abundance of coal deposits has resulted in coal playing a very significant role in meeting South Africa’s energy needs, it accounts for 90% of South Africa’s energy supply. On the other hand, the negative impact that the exploitation of coal continues to have on the environment poses serious challenges to South Africa’s continued over-reliance on coal as the foundation of the country’s energy sector. The universally accepted consensus is that greenhouse gas emissions must be kept to a minimum and the continuing over-reliance on coal, in the way it is currently processed, goes counter to this. The renewable energy sector in South Africa is still at a nascent stage, how it develops is going to be important in determining whether South Africa is successful in meeting her energy needs in an environmentally clean and sustainable manner whilst at the same time maintaining an acceptable degree of energy security. The critical balance between mitigating against the negative effects of being a coal intensive energy economy and maximizing the generation and intake of renewable energy onto the grid will only be achieved on the back of a sound regulatory framework, made up of articulate and effective laws.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research at the University of the Witwatersrand, Johannesburg 2018
Keywords: Energy industries--Law and legislation--South Africa; Renewable energy sources--Law and legislation